Flexible endoscopic evaluation of swallowing (FEES) to determine neurological intensive care patients' oral diet. (2nd January 2021) - Braun, Tobias; Juenemann, Martin; Viard, Maxime; Meyer, Marco; Reuter, Iris; Mausbach, Stefan; Doerr, Johanna M.; Schirotzek, Ingo; Prosiegel, Mario; Schramm, Patrick; Kaps, Manfred; Tanislav, Christian
Abstract: Purpose: Dysphagia is common in critically ill neurological patients and is associated with a high mortality and morbidity. Data on the usefulness of flexible endoscopic examination of swallowing (FEES) in neurological intensive care unit (ICU) patients are lacking, raising the need for evaluation. Method: FEES was performed in neurological intensive care patients suspected of dysphagia. We correlated findings with baseline data, disability status, pneumonia and duration of hospitalisation, as well as a need for mechanical ventilation or tracheotomy. Result: This analysis consisted of 125 patients with suspected dysphagia. Most of the patients (81; 64, 8%) suffered from acute stroke. Dysphagia was diagnosed using FEES in 90 patients (72%). FEES results led to dietary modifications in 80 patients (64%). The outcome at discharge was worse in dysphagic stroke patients diagnosed by FEES as compared to non-dysphagic stroke patients ( p  = 0.009). Patients without oral diet had higher need for intubation ( p  = 0.007), tracheotomy ( p  = 0.032) and higher mortality ( p  < 0.001) in comparison to patients with at least small amounts of oral intake. Conclusion: As the clinical assessment of the patients often classified the dysphagia incorrectly, the broad use of FEES in ICU patients might help to adequately adjust patients' oral diet. This knowledge might contribute to lower mortality and morbidity.